2022
DOI: 10.1002/ese3.1149
|View full text |Cite
|
Sign up to set email alerts
|

Solar photovoltaic potential and diffusion assessment for Pakistan

Abstract: In Pakistan, around 58% of current electricity is generated from fossil fuels and only 2.4% is generated using renewable energy (RE) resources even though country is blessed with enormous RE potential. Among other RE resources, Pakistan's geographical location offers high solar energy potential, which implies that actual potential assessment should be undertaken. This study, as such, undertakes a comprehensive assessment of solar energy potential and prospects of solar photovoltaic (PV) systems for both off-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The country receives 8 to 10 h of sunlight each day in most of its regions, which receive an average of 15.5 to 1014 KWh of solar radiation annually, with 20 MJ/m of solar insulation and an average of 8.5 h of sunlight every day [48]. The province of Baluchistan has one of the highest potentials for sun irradiation, according to [49]. In addition, there is significant potential for solar energy production in the deserts of Punjab, Sindh, and Baluchistan.…”
Section: Pakistan's Fossil Fuels and Renewable Energy Potential And R...mentioning
confidence: 99%
See 1 more Smart Citation
“…The country receives 8 to 10 h of sunlight each day in most of its regions, which receive an average of 15.5 to 1014 KWh of solar radiation annually, with 20 MJ/m of solar insulation and an average of 8.5 h of sunlight every day [48]. The province of Baluchistan has one of the highest potentials for sun irradiation, according to [49]. In addition, there is significant potential for solar energy production in the deserts of Punjab, Sindh, and Baluchistan.…”
Section: Pakistan's Fossil Fuels and Renewable Energy Potential And R...mentioning
confidence: 99%
“…In addition, there is significant potential for solar energy production in the deserts of Punjab, Sindh, and Baluchistan. This land is perfect for solar installations because it is fertile and cannot be used for anything else [49]. Around 1600 GW per year, which is more than 40 times the capacity of the existing power generation system, is the estimated solar potential [50].…”
Section: Pakistan's Fossil Fuels and Renewable Energy Potential And R...mentioning
confidence: 99%
“…The main heat flow or waste heat energy of this system can be output and transformed into electric energy . The investigation reports that 2.8 × 106 GWh of electricity in Pakistan is available annually . Awais et al utilized RET Screen software to simulate a photovoltaic system, and the study showed that the designed model was sufficient to provide the required electrical power for the area and transfer any surplus energy to the grid due to the abundant solar energy resources in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…10 The investigation reports that 2.8 × 106 GWh of electricity in Pakistan is available annually. 11 Awais et al 12 utilized RET Screen software to simulate a photovoltaic system, and the study showed that the designed model was sufficient to provide the required electrical power for the area and transfer any surplus energy to the grid due to the abundant solar energy resources in Pakistan. Economic studies have indicated that the power system will start generating profits after 7.4 years from installation and will continue to do so until the 25th year of the life of the project.…”
Section: Introductionmentioning
confidence: 99%
“…The PV sector has increased by over 35% annually over the last decade. Global PV capacity was 591 GW in 2019, including 184 GW of module manufacture and 125 GW of sales (Feldman and Margolis, 2019;Khatri et al, 2022). Current solar technology comprises PV and solar thermal panels, which are combined to generate electricity and heat in hybrid PV/T systems (Barbu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%